2011
DOI: 10.1111/j.1463-6409.2011.00480.x
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking the evolution of extant sub‐Saharan African suids (Suidae, Artiodactyla)

Abstract: G. (2011). Rethinking the evolution of extant subSaharan African suids (Suidae, Artiodactyla). -Zoologica Scripta, 40, 327-335. Although African suids have been of scientific interest for over two centuries, their origin, evolution, phylogeography and phylogenetic relationships remain contentious. There has been a longrunning debate concerning the evolution of pigs and hogs (Suidae), particularly regarding the phylogenetic relationships among extant Eurasian and African species of the subfamily Suinae. To inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 35 publications
(63 reference statements)
6
58
1
Order By: Relevance
“…On the other hand, Eurasian γ1 ERVs showed a less conserved arrangement in all phylogenies, with internal groups not corresponding to the host phylogeny [22,23] except for the env class B internal arrangement, which was very similar in the host phylogeny (highlighted in Figure 4). …”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, Eurasian γ1 ERVs showed a less conserved arrangement in all phylogenies, with internal groups not corresponding to the host phylogeny [22,23] except for the env class B internal arrangement, which was very similar in the host phylogeny (highlighted in Figure 4). …”
Section: Resultsmentioning
confidence: 99%
“…Within Kolpochoerus, we restrained our analysis to species from eastern Africa for which sufficient complete cranio-mandibular material is available. A recent phylogenetic analysis revealed the Eurasian genus Sus to be the sister group of African suids, and Babyrousa to be the basalmost taxon within the subfamily Suinae (Gongora et al 2011). We therefore used Babyrousa as outgroup, and included Sus scrofa in our analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Although recent molecular studies have shown extant African suids to form a monophyletic group, with Hylochoerus and Phacochoerus forming a clade to the exclusion of Potamochoerus (Gongora et al 2011), relatively little is known about their origin and evolutionary history, owing to their patchy fossil record and the uncertain taxonomic and phylogenetic status of most of their fossil relatives. Potamochoerus in particular has traditionally been used as a wastebasket taxon for many archaic-looking specimens characterized by simple, short, brachyodont and bunodont teeth, resulting in general confusion regarding the antiquity of this genus (White 1995;Bishop 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In summary, recent molecular biology studies of suids indicate that the so-called Warty Pigs (Dasychoerus) and Bearded Pig (Euhys) are more closely related to each other, than any of them are to the Wild Boar (Sus scrofa) (Gongora et al 2010;Frantz et al 2013) or to Phacochoerus (the outgroup in the study by Frantz et al 2013). On the basis of the fossil record, Pickford (2013e) postulated that the Wart Hog lineage (Phacochoerus) split from the Warty Pig lineage (Dasychoerus) during the Late Miocene which would accord with the molecular data.…”
Section: Boreal Subtropical and Tropical Suidsmentioning
confidence: 98%
“…For this reason, rates of evolution in suines requires further study, but at present, the fossil record seems to support the notion that r-strategists such as Sus scrofa evolved more slowly than K-strategists such as Phacochoerus. the studies (Wu et al 2006;Funk et al 2007;Gongora et al 2010;Frantz et al 2013 Groves & Grubb 1993): 1) non-warty pigs (Sus scrofa and Porcula salvania Hodgson, 1847); and 2) warty pigs (all other species of "Sus"). Subdivision on the basis of lower canine morphology yields almost the same categories except that the "warty" subgroup is capable of further subdivision into two clusters: 2a) the philippensis group; and 2b) the verrucosus group.…”
Section: Boreal Subtropical and Tropical Suidsmentioning
confidence: 99%